2024
DOI: 10.3390/ijms25074126
|View full text |Cite
|
Sign up to set email alerts
|

Soluble NKG2DLs Are Elevated in Breast Cancer Patients and Associate with Disease Outcome

Anna Seller,
Christian M. Tegeler,
Jonas Mauermann
et al.

Abstract: Ligands of the natural killer group 2D (NKG2DL) family are expressed on malignant cells and are usually absent from healthy tissues. Recognition of NKG2DLs such as MICA/B and ULBP1-3 by the activating immunoreceptor NKG2D, expressed by NK and cytotoxic T cells, stimulates anti-tumor immunity in breast cancer. Upregulation of membrane-bound NKG2DLs in breast cancer has been demonstrated by immunohistochemistry. Tumor cells release NKG2DLs via proteolytic cleavage as soluble (s)NKG2DLs, which allows for effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…Although several studies have shown that γδT cells can modulate immunosuppressive cells within the TME, the scarcity of nutrients, the presence of suppressor molecules, and hypoxia may still constrain their therapeutic potential ( 142 , 143 ). Suppressive molecules produced by tumor cells and other cells in the TME, such as TGF-β ( 144 ), prostaglandin E2 (PGE2) ( 145 ), adenosine ( 146 ), and soluble NKG2D ligands ( 147 ), can interfere with γδT cell proliferation and function.…”
Section: Major Challenges and Clinical Implications Of Utilizing γδT ...mentioning
confidence: 99%
“…Although several studies have shown that γδT cells can modulate immunosuppressive cells within the TME, the scarcity of nutrients, the presence of suppressor molecules, and hypoxia may still constrain their therapeutic potential ( 142 , 143 ). Suppressive molecules produced by tumor cells and other cells in the TME, such as TGF-β ( 144 ), prostaglandin E2 (PGE2) ( 145 ), adenosine ( 146 ), and soluble NKG2D ligands ( 147 ), can interfere with γδT cell proliferation and function.…”
Section: Major Challenges and Clinical Implications Of Utilizing γδT ...mentioning
confidence: 99%